Applied aspects of the concept of macrofinancial imbalances management - Radionova, Iryna; Malkovska, Yuliia; Радіонова, Ірина Федорівна (OÜ Scientific Center of Innovative Research, 2022)
This paper addresses the important scientific problem of public administration: the concept of managing macrofinancial imbalances in the Ukrainian economy. Applied aspects of the concept, according to the authors, mean, first of all, answers to two questions: how to assess imbalances, and what is the participation of authorities in their regulation. The authors identified imbalances and divided them into two major groups: 1) imbalances associated with the active phase of the Russian-Ukrainian war, which began in February 2022, and 2) imbalances resulting from Ukraine's current economic model. It is concluded that the concept of institutional design of macrofinancial stability of the Ukraine’s national economy should be altered. The reasons for this conclusion are based on the examination of data on national economic security levels achieved between 2010 and 2021, the institutions involved in the management of macrofinancial imbalances in Ukraine, and the experience of imbalance management in the European Union (EU). The authors proceed from the idea that the concept of institutional design of macrofinancial stability, among other things, includes: 1) a system of indicators for assessing (detecting) imbalances and monitoring them, and 2) a system of public authorities that interact to perform the management process. The article substantiates the so-called Ukrainian scoreboard, which consists of 14 indicators for assessing (detecting) macrofinancial imbalances. The proposed scoreboard of indicators is justified, first and foremost, by the expedience of approaching the system of imbalance assessment (detection) used in the EU. Second, the indicators must reflect the unique challenges that Ukraine faces. Such criteria for selecting indicators, according to the authors, lay the groundwork for ensuring a sufficient level of future economic security. The authors also propose approval of the list of 28 auxiliary indicators, the use of which will contribute to an adequate policy response to imbalances in the Ukrainian economy and changes in institutional design through changes in the competencies and limits of responsibility of institutions public authority.
Keywords: concept; imbalance management; macrofinancial imbalances; institutional design; scoreboard of indicators; stability of the national economy; national economic security